Supporting Social Justice Advocacy: A Paradigm Shift towards an Ecological Perspective - Arie T. Greenleaf; Joseph M. Williams (Journal for Social Action in Counseling and Psychology)
The entrenched intrapsychic perspective that currently dominates the counseling professions does not philosophically support social justice advocacy. Because an intrapsychic approach to counseling focuses almost exclusively on change at the individual level, interventions to change an oppressive environment are routinely ignored. Thus, this manuscript presents the argument that a paradigm shift towards an ecological perspective, one that recognizes human behavior as a function of person-environment interaction, is necessary to provide practitioners a clear rationale to engage in social justice advocacy in counseling.